Унификация геометрии рабочих поверхностей зубьев при синтезе передач зацеплением - Воронцов, Б. С.; Бочарова, И. А.; Чаплинский, Д. А. (НТУ "ХПИ", 2008)
Розглядаються комп'ютерно-графічний і аналітичний способи апроксимації таблично представлених кривих, що описують профіль зубців. Для уніфікації геометрії робочих поверхонь зубців використовуються криві Без’є третього порядку. Отримані результати дозволяють підвищити ефективність систем автоматизованого синтезу й аналізу передач зачепленням.

Computer-aided-drawings and analytical methods of approximation of presented in the tables curves which describes teeth profile have been investigated. To unify geometry of teeth working surfaces Bezie curves of the third power have been used. The obtained results allow for the increase of effectiveness of automate synthesis and analysis of gearing.
Keywords: производящая поверхность; кривые Безье; построение; аппроксимация